Effect of Slaughter Age and Sex on Carcass Characteristics and Composition of Macherla Brown Sheep - Vinaya Babu, P.; Rao, B. Eswara; Rao, T. Srinivasa (Journal of Meat Science, 2014)
Twenty four local Macherla Brown lambs of both sexes in the age group of 9 and 12 months were slaughtered to study the carcass characteristics and composition. Pre-slaughter weight, dressing percent and carcass weight were significantly (P<0.01) higher at 12 months of age than 9 months. Dressing percent on pre-slaughter weight was significantly (P<0.01) higher in males compared to females. Except for dressing percent all the other carcass traits and byproducts yield varied insignificantly (P<0.01) between male and female lambs. Moisture content was significantly (P<0.01) lower and protein content was significantly higher as age of animal advanced from 9 to 12 months. However, no differences were observed significantly in fat and ash contents. The study showed that sex had no influence on proximate composition of meat from Macherla Brown sheep. It was concluded from the study that slaughter age of 12 months was found to be superior for quantitative and qualitative meat production.